Efficacy of acupuncture for generalized anxiety disorder: A PRISMA-compliant systematic review and meta-analysis. Issue 49 (9th December 2022) - Li, Meichen; Liu, Xin; Ye, Xinyi; Zhuang, Lixing
Abstract : Background: Generalized anxiety disorder (GAD) tightly traps modern people. Its incidence shows an increased peak during the 2019 novel coronavirus (COVID-19) epidemic. Acupuncture is regarded as an effective way to relieve anxiety symptoms. However, there are still controversies. This study aimed to systematically evaluate the clinical efficacy of acupuncture in patients with GAD. Methods: Four English and 3 Chinese databases were searched from their inception to January 2022. Only randomized controlled trials (RCTs) in which acupuncture was the main intervention were included. The literature was independently screened and extracted by two investigators. The Cochrane Bias Risk Assessment Tool was used for quality evaluation. Analyses were conducted by RevMan 5.3.0 and STATA 15.0 software. The primary outcome was the Hamilton Anxiety Scale (HAMA). The secondary indicators were the total effective rate, the Self-Rating Anxiety Scale (SAS), and the Treatment Emergent Symptom Scale (TESS). Results: Twenty-seven studies were included with a total of 1782 participants. The risk of performance bias or reporting bias for most of the included trials was unclear. Combined results showed the acupuncture group had better outcomes in the HAMA score [MD = −0.78, 95%CI (−1.09, −0.46)], the total effective rate [RR = 1.14, 95%CI (1.09, 1.19)], the SAS score [MD = −2.55, 95%CI (−3.31, −1.80)] compared with the control group. Regarding the number of adverse events, the acupuncture group was safer than the control group and scored less grade in the TESS score [MD = −1.54, 95%CI (−1.92, −1.17)]. Conclusions: Acupuncture can effectively relieve the anxiety symptoms of generalized anxiety disorder patients with fewer side effects, but randomized controlled trials with large sample size and high quality are also required to support the result.